Long-term safety evaluation of natalizumab for the treatment of multiple sclerosis. Issue 8 (3rd August 2017) - Clerico, Marinella; Artusi, Carlo Alberto; Di Liberto, Alessandra; Rolla, Simona; Bardina, Valentina; Barbero, Pierangelo; De Mercanti, Stefania Federica; Durelli, Luca
ABSTRACT: Introduction : Natalizumab is a humanized monoclonal antibody highly effective in relapsing-remitting multiple sclerosis (MS). Important concerns about its safety have been pointed out mainly because of the risk of progressive multifocal leukoencephalopathy (PML), caused by the opportunistic John-Cunningham virus (JCV). Areas covered : This review analyzes all the safety aspects related to the use and safety of natalizumab in MS patients. Other than PML, post-marketing, safety red-flags have been reported, as liver or haematological serious adverse events. Pregnancy evidences will be pointed out. The risk of PML depends on: concomitant or previous immunosuppression, exposure duration, anti–JCV antibody level. In natalizumab-related PML the average survival is 77%; prognostic features and information for the earliest identification of PML have been identified to maximally reduce its incidence, mortality and morbidity. Expert opinion : Natalizumab is a highly effective drug for MS patients but its safety issues represent a relevant limitation and impose strict clinical surveillance of treated patients. Some post-marketing safety red-flags have been pointed out, with higher attention to severe liver failures and limphoma cases. If PML and its consequences are considered the most relevant issues, a continuous surveillance must be maintained also regarding other possible SAEs like liver diseases and malignancies.